The Transformative Role Of The Al-Hanafiyah Religious Council In Improving The Religious Understanding Of The Muslim Community In Karawang - Alandes, Pirdaus; Akil, Akil; Susanto, Agus (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to analyze the transformational role of majelis taklim in enhancing the religious understanding of the Muslim community. Majelis taklim, as a non-formal Islamic educational institution, has a strategic role in shaping character, deepening religious knowledge, and strengthening Islamic practices in daily life. For clarity, this abstract is written in a more concise and structured paragraph. This study uses a qualitative approach with a case study method in majelis taklim that are active in the Karawang area. Data were collected through in-depth interviews, participatory observation, and documentation of activities. The results show that majelis taklim function not only as a means of religious learning but also as a forum for spiritual, social, and moral guidance for the community. Through a transformational approach, majelis taklim are able to change the mindset of their members from merely acquiring religious knowledge to practicing substantive and contextual Islamic values. The addition of terms such as transformative learning, religious awareness, and community-based Islamic education clarifies the scope of the research. Factors supporting success include the charismatic leadership of ustaz/ustazah, the relevance of the study material, and the active involvement of the community. The implications of the research indicate that majelis taklim need to be strengthened as agents of socio-religious transformation through the development of a study curriculum that is relevant to the needs of modern society. The research recommendations emphasize the need for capacity building training for teachers and strengthening collaboration between majelis taklim and other religious institutions to expand the impact of education.